Executability of the Constitutional Court's formal testing decision: Indonesia's Omnibus Law review - Saputra, Rian; Zaid, M; Triasari, Devi (Journal of Law, Environmental and Justice, 2023)
This legal writing analyses the incoherence in the use of Government Regulations in Lieu of Laws as an implementation of the Constitutional Court's Decision on the Formill Test of Laws by using Constitutional Court Decision Number 91 / PUU-XVIII / 2020 as a study material and trying to describe future precedents to the formal test decision, which Perpu continues to improve. It uses case, statute, and conceptual approaches to conduct normative legal research. The study found that: a. The Constitutional Court Decision Number 91/PUU-XVIII/2020 declared the Job Creation Law conditionally unconstitutional because its formation was not based on reasonable and correct procedures for the formation of laws and regulations or radically deviated from the principle of lawmaking. Constitutional Court Decision Number 91/PUU-XVIII/2020 requested that the Job Creation Law, which was declared conditionally unconstitutional, be revised through a good and correct mechanism for law and regulation formation, which includes community participation. In the context of the president's attitude towards using Government Regulation in Lieu of Law to comply with the Constitutional Court Decision No. 91/PUU-XVIII/2020, the use of the Perpu mechanism to improve the Job Creation Law negates public participation as a fundamental part of the process of forming good laws and regulations.